A pilot study on the impact mechanism of internal and external leading variables on consumers’ purchase intention and healthy dietary behavior of plant-rich foods - Limin Fang; Shahriman Zainal Abidin; Lesi Zhou; Juncheng Mu; Honglei Lu (PLoS ONE, 2026)
This study integrates the TPB with Information Processing Theory and Sensory Marketing Theory to investigate the influence mechanisms of Plant-Rich Foods(PRF) attributes and their packaging on consumer purchase intention and healthy eating behaviors. Through the construction of a structural equation model, empirical analysis was conducted on seven core variables and their interrelationships: consumer attitude(CA), socio-cultural environment(SE), consumer individual requirements(CIR), packaging environmental considerations(ECP), perceived experiential value(PEV), food information factors(FIF), and packaging functional attributes(FPP), thereby validating the proposed hypotheses. The results indicate that all seven variables significantly and positively influence purchase intention, albeit with varying strengths. Packaging functional attributes demonstrated the strongest driving force, followed by individual consumer needs and food information factors. Perceived experiential value, consumer attitude, and packaging environmental considerations exhibited moderate influence, while the socio-cultural environment exerted the weakest impact. The overall influence of “externally oriented” product variables on purchase intention surpassed that of “internally oriented” consumer variables. The impact on healthy eating behaviors presented a dual logic of “direct drive and indirect transmission.” consumer individual requirements exhibited a weaker direct influence on healthy eating behaviors compared to their influence on purchase intention, forming a chained transmission pathway from individual needs to purchase intention to healthy behaviors. Theoretically, this research extends the application of the Theory of Planned Behavior, elucidates the transmission mechanisms of variables, and constructs a multidimensional relational framework. Practically, it offers direction for plant-based food enterprises in optimizing packaging and marketing communication strategies, and provides a reference basis for policymakers.